Recursos educacionais abertos no formato audiovisual: fluência tecnológico-pedagógica em softwares livres - Jorge, Loren Kellen Carvalho (2018)
This research is situated in the area of concentration of the Educational Technologies Network for Innovation and Democratization of Education, in the line of research of the Educational Network Technologies Management. The main goal of this research is to promote the Technological-Pedagogical Fluency (TPF) in open source software to increase the production of Open Educational Resources (OER) in the audiovisual format.The theme is related to the expension and development of the OER in the audiovisual format in the higher education field, enabling and promoting authorship and co-authorship. The survey was qualitative, with directly applied research, with procedures based on the methodological approach of the Design-Based Research (DBR) iterative cycles. There were done four workshops about the production of OER using the audiovisual format. Those activities happened after the evaluation and choice stage of Kazam, an open source software, which the criteria emphasized the types of extension of the files created and the compatibility of the operational systems, enabling the reuse. Besides the participant observation, the data was also collected with the application of questionnaires (diagnostic and evaluative ones). From the data analysis, it was concluded that the interventions achieved the goal of promoting the TPF to increase the production of video lessons with open source softwares. However, it is worthy of mention the need to disseminate the initiative to other environments. It was identified the resistance from most of the participants envolved in the reasearch, because even orally demonstrating that there was comprehension about the inovation with the OER to the integration of the open source softwares, many participants continued to use paid sofwares. It can be concluded that this is due to the familiarity with computer softwares that have already been used more frequently, besides the technical and practical effort that is required to learn how to manage new softwares. This, in turn, impplies challanges to reach emancipatory levels of TPF that allow to think about the practice itself and to collaborate with other people from the open network movement. To enable the democratic expansion of the knowledge implemented in the workshops, there were created products from both theoretical and practical nature. The product with theoretical approach is an electronic institutional guide called “Handbook: Video Lesson Production with Open Source Softwares” (“Guia: Produção de Videoaulas com Softwares Livres”). In the group of product with practical approach, there are: a video class tutorial about Kazam; a commented video about the potential of video class; a model of script about video class production; a Kazam software user’s guide; the teaching material about video class production from the workshops.